Conservation of Amazonian manatee (Sirenia: Trichechidae): the case of Extractive Reserve Verde para Sempre, Brazil - Hoffmann, Cinthia; da Silva, Samantha; Rodrigues, Angélica; Baía-junior, Pedro; Le Pendu, Yvonnick; Guimarães, Diva Anelie (Ethnobiology and Conservation, 2020)
The Amazonian manatee (Trichechus inunguis) is the largest aquatic freshwater mammal in South America found in the main rivers of the Amazon Basin. The main objective of this work was to describe the ecological knowledge and use of the Amazonian manatee in the Extractive Reserve Verde para Sempre (RESEX), located in Porto de Moz, Pará, Brazilian Amazon. This study was conducted through semi-structured interviews, free interviews, participant observation and image capture. Thirty-one residents were interviewed in 21 RESEX communities. The interviewees were previously identified by local informants and selected according to their level of knowledge of the species. We collected information on the morphology, behavioral characteristics and feeding habits of manatees, as well as on the uses of the species. According to interviewees, poaching and consumption of manatees is rare, and entanglement of calves in fishing nets is accidental. The headwaters of rivers and streams, that make up the water network of this extractive reserve, are little affected by human activity, and constitute potential areas of refuge for the species. The study shows that the maintenance of the extractive reserve gives good results in the protection of the Amazonian manatee. Even though, these animals are accidentally caught, and sometimes poached. Thus, it corroborates with the statement that sustainable development reserves are efficient strategies for biodiversity conservation. Thus, it is suggested the application of environmental education programs and awareness measures, aimed at the general public.